Development of Jumanji Mathematics Cultural Diversity-Based Board Game Learning Media - Azis, Zainal (Al'Adzkiya Journal, 2024)
This research is a study on the development of culturally diverse-based learning media. The purpose of this research is to understand how the development of Jumanji Mathematics board game learning media based on cultural diversity is carried out. Additionally, it aims to assess the suitability of culturally diverse-based learning media and to gauge student responses in terms of their interest in the developed learning media. The development model used in this research is the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. During the implementation stage, the researcher conducted product testing in one class, specifically class VII-B, with a total of 21 students. The results of this research show that the Jumanji Mathematics board game learning media developed based on cultural diversity has a validity level of 3.07 as assessed by media experts. The assessment of the content received a score of 4, indicating it is highly valid. The practicality level falls into the category of very practical, with an average score of 3.62.